Pessoas com Deficiência Intelectual em processo de envelhecimento: entendimentos de profissionais especializados - Boniholi, Gabriela Ishikawa (Universidade Federal de São Carlos, 2022)
This research aimed to analyze the perspectives of professionals involved in the care of individuals with intellectual disabilities who are aging, focusing on their understanding of this life stage and established conceptions regarding disability, aging, and their own role in activities of daily living. The main objective was to investigate the understanding of professionals working with individuals with intellectual disabilities aged forty (40) and above, regarding functionality in this stage of life, as well as their perceptions of aging and disability. Specific objectives included: (a) analyzing the functioning of institutions catering to individuals with disabilities in this life stage; (b) exploring how independence in daily life tasks is perceived by these professionals; and (c) examining the role of these professionals in the care of this population. Nine professionals working in special education institutions - referred to as Institution A and B - where adults with intellectual disabilities aged forty (40) and above are located, participated in this research. The professionals included caregivers and healthcare professionals such as physiotherapists, occupational therapists, and gerontologists. Data collection involved semi-structured interviews, and the results were analyzed and categorized into four main themes: (a) Concept of Disability; (b) Aging and Disability; (c) Disability, Aging, and Independent Living; and (d) Professional Roles. These findings were then discussed in line with existing literature in the field. The data gathered indicated that professionals observed signs of premature aging among individuals with intellectual disabilities in both institutions. There were still stigmas regarding the understanding of the concept of "disability" among some interviewed professionals, which could hinder the development of activities aimed at promoting independence due to a perception of dependence. Additionally, the lack of specific training in working with individuals with intellectual disabilities among these professionals was evident, highlighting another factor contributing to the absence of quality care.
People with Intellectual Disabilities in the aging process: perspectives of specialized professionals
Keywords: Educação Especial; Deficiência intelectual; Envelhecimento; Profissionais especializados da saúde; Cuidadores; Special Education; Intellectual disability; Aging; Healthcare specialists; Caregivers; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL